Exploring the role of nutrition in mental health: A narrative review - Bhat, Neeti; Dahal, Aashma; Shakya, Yojana; Dhungana, Nisha (Journal of Psychiatrists' Association of Nepal, 2023)
Global burden of disease 2020 indicates that unipolar depression contributes the second most to increased DALY (disability-adjusted life years) worldwide, but it wasn't even on the top fifteen list in the 1990s. While some mental health problems may warrant pharmacological intervention, non-drug lifestyle behaviors also popularly known as lifestyle medicine and mental health tools present a promising avenue for mitigating depressive symptoms. Lifestyle psychiatry, a growing field pertains to lifestyle pillars such as diet, physical activity, stress, and sleep and their role in psychiatric disorders. Nutrition, a fundamental core in lifestyle medicine, presides over virtually all chronic diseases. Describing nutrition and mental health is challenging, and studies of their interactions are even more complex. Nevertheless, gut microdata are critical to understanding this relationship. Thus, this narrative review aims to unravel the role of nutrition in the context of selected mental disorders. Simultaneously, it aims to empower practitioners and readers of Nepal to make informed lifestyle decisions regarding their nutritional choices. Additionally, it seeks to play as well as play a contributory role in the advancement of nutritional psychiatry as a discipline.